Effect of Ochratoxin A (OTA) on the Immune System: A Systematic Review - Yusif Mubarik; Shadrach Tetteh Boyetey; Anastasia Rosebud Aikins; Mohamed Mutocheluh (Toxins)
Ochratoxin A (OTA) is a mycotoxin with different adverse health effects. The authors conducted a systematic review to evaluate the effects of OTA on the immune system, with more emphasis on its effects on immune system organs, innate and adaptive immunity and related signaling pathways. Studies have demonstrated that exposure to OTA disrupts the functions of immune system organs, resulting in weight loss, histological lesions and a decrease in antibody-secreting cells. There is evidence that OTA impairs epithelial barrier integrity and macrophage function and induces elevated secretion of pro-inflammatory cytokines. In adaptive immunity, OTA regulates T-cell differentiation, particularly Th1 and Th17 subsets, and adversely impacts humoral immunity, ultimately leading to immune suppression.